PENAMBAHAN SERBUK LIMBAH KACA DAN ABU DAUN BAMBU TERHADAP KINERJA PAVING BLOCK - Anita Intan Nura Diana; Subaidillah Fansuri (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Glass is an object that cannot be separated from human life. Based on data from the Minister of Environment and Forestry (LHK) in 2020, it was stated that data on waste in Indonesia reached 67.8 million tons, of which 0.7 million tons were glass waste. It is known that the types of waste produced in Indonesia are organic waste (60%), plastic waste (14%), paper waste (9%), metal (4.3%), glass and wood (12.7%). The purpose of this study was